Influência do ciclo estral na maturação nuclear de oócitos caninos - Pereira, L. M.C. [UNESP]; Bersano, P. R.O. [UNESP]; Lopes, M. D. [UNESP] (My University, 2013)
The aim of this study is to evaluate the relationship between the phases of diestrus and anestrus with nuclear maturation of canine oocytes. A total of 36 female dogs, subject to elective ovariohysterectomy in Clinic of Small Animal Reproduction FMVZ / UNESP, Botucatu. Ovaries were sliced and selected cumulus-oocyte complexes (COCs) degree 1. COCs were cultured in maturation medium for 72 h, subjected to hyaluronidase solution 0,2% and stained with Hoechst. The oocytes were evaluated by light microscopy and fluorescence. The Fisher exact test was used to estimate the association between the estrous cycle and nuclear maturation. The results showed no significant difference (p>0,05) between rates of maturation of oocytes of different stages.
Influence of estrous cycle in nuclear maturation of canine oocytes
Keywords: Bitches; Estrous cycle; Nuclear maturation; Oocytes